Analisis Penggunaan Sosial Media Influencer Dalam Meningkatkan Brand Image Suatu Produk (Studi Kasus Pada Mie Uda Bro Padang) - Martin, Robi; Eriend, Dion (CV. ITTC INDONESIA, 2024)
This research aims to find out how to use social media influencers to improve the brand image of Mie Uda Bro Padang, both by determining influencers and the criteria for influencers that will be used so that the target to be achieved from using influencers in promoting products can be achieved in accordance with the specified targets. In describing this research, the researcher uses celebrity endorser theory. In this theory, it is explained that endorsers consist of five attributes which are described with the abbreviation TEARS, where TEARS are Trustworthiness, Expertise, Physical attractiveness, Respect, Similarity. This research uses a descriptive qualitative method, this is because this type of research is collected in the form of words, images, not numbers. Mie Udabro has criteria in determining which influencers to use in promoting their products on social media. The criteria determined also aim to ensure that the results obtained after advertising products through social media influencers are also beneficial for service users such as increasing the number of consumers, increasing the number of followers on social media, as well as to achieve sales targets.When carrying out promotions using Influencers, mie Udabro has criteria for determining which influencer services to use. And in determining the influencer criteria used by Mie Udabro, they have applied the influencer criteria explained.